A New Global Air Quality Health Index Based on the WHO Air Quality Guideline Values With Application in Cape Town - Temitope Christina Adebayo-Ojo; Temitope Christina Adebayo-Ojo; Janine Wichmann; Oluwaseyi Olalekan Arowosegbe; Oluwaseyi Olalekan Arowosegbe; Nicole Probst-Hensch; Nicole Probst-Hensch; Christian Schindler; Christian Schindler; Nino Künzli; Nino Künzli; Nino Künzli (Frontiers Media S.A., 2023)
Objectives: This study developed an Air Quality Health Index (AQHI) based on global scientific evidence and applied it to data from Cape Town, South Africa.Methods: Effect estimates from two global systematic reviews and meta-analyses were used to derive the excess risk (ER) for PM2.5, PM10, NO2, SO2 and O3. Single pollutant AQHIs were developed and scaled using the ERs at the WHO 2021 long-term Air Quality Guideline (AQG) values to define the upper level of the "low risk" range. An overall daily AQHI was defined as weighted average of the single AQHIs.Results: Between 2006 and 2015, 87% of the days posed "moderate to high risk" to Cape Town's population, mainly due to PM10 and NO2 levels. The seasonal pattern of air quality shows "high risk" occurring mostly during the colder months of July-September.Conclusion: The AQHI, with its reference to the WHO 2021 long-term AQG provides a global application and can assist countries in communicating risks in relation to their daily air quality.